Carbon Management in Forest Floor - an Agenda of 21st Century in Indian Forestry Scenario - Ramachandran, A.; Jayakumar, S.; Haroon, A. R. Mohamed; Bhaskaran, A. (Indian Forester, 2007)
In response to growing concern on global climatic change, carbon management in forests is inevitable in order to offset the carbon emission in the atmosphere. Forests act as a sink for the CO2 to mitigate the global climatic change. In developing countries like India, due to various need based forest management practices, cultivations, forest fire, etc, there has been a continuous loss of original biodiversity and soil. These degradations led to a loss of sequestered carbon of standing biomass and in the soil as well. The total area under forest cover in Kolli hills is about 27,103 ha. The total biomass carbon estimated is about 2.74 Tg. The total SOC estimated in the forest area is about 3.18 Tg. The ratio between the biomass carbon and SOC is much less than the tropical forests of the world. This indicates that there has been a heavy degradation of forest especially of forest soil. Hence, restoration of soil organic carbon (SOC) lost over the period of time due to anthropogenic interferences has to be built up and maintained with minimum threshold to support the tree growth. A pioneer attempt is made to identify the minimum threshold of surface SOC to the level of 1.2% to be maintained in the forest floor. This paper analyzes the intricacies of biomass carbon and SOC in a degraded condition. Detailed strategies for sustainable management of these degraded forests are discussed.